Plea Bargaining In India : An Overview - Krishnapal Singh Chauhan (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2015)
Oxford Dictionary defines "plea" as an appeal, prayer, request, or formal statement made by or on behalf of the defendant, and "bargaining" as a negotiation, settlement, contract, or accord. As a result, the phrases "bargaining" and "plea" are used interchangeably in this sentence. The accused may make a formal statement or appeal as part of a plea agreement that is negotiated with the victim and the prosecution. In other terms, we may say that a plea agreement is a contract made between the prosecutor and the defendant in which both parties agree to resolve the legal matter and the defendant promises to confess guilt in exchange for receiving the least severe punishment possible for the offence. Plea bargaining can happen at any point before a judgment is issued, but it typically takes place before trial.